THE EFFECT OF KNOWLEDGE NETWORK, KNOWLEDGE INTEGRATION AND RELATIONAL CAPITAL ON INNOVATION CAPABILITY - Detha Alfrian Fajri; Siti Barokah (Universitas Brawijaya, 2020)
This study aims to determine and analyze the effect of intellectual capital on innovation capability. This study uses a quantitative approach. The independent variables are knowledge network, knowledge integration and relational capital. The dependent variable is the company's innovative capabilities. In this study using a questionnaire with 17 questions. This study had 32 respondents from different startup companies in Indonesia. Analysis of the data used in the form of validity and reliability statistics, classical assumption tests, and multiple linear regression analysis. The results of the study show knowledge network has a significant effect on knowledge integration. Knowledge integration and relational capital also have a significant effect on innovation capability.